Policy Collaboration at the Local Level: A Case Study of Urban Waste Management in Rawalumbu District, Bekasi - Destrilia, Intan; Perdanaputra, Decky; Fahmi, Ade (Universitas Sang Bumi Ruwa Jurai, 2022)
This study examines the dynamics of policy collaboration in urban waste management in Rawalumbu District, Bekasi City. As urban populations grow and waste generation increases, local governments must partner with community organizations, private actors, and informal sectors to address public service challenges. Using a qualitative case study approach, this research analyzes how collaboration is initiated, managed, and sustained between stakeholders in implementing a community-based waste management program. The findings reveal key enabling and constraining factors in local policy collaboration, such as trust, resource-sharing, and leadership. Recommendations are offered to enhance multi-actor governance at the sub-city level.